1991
DOI: 10.1107/s0108270190010332
|View full text |Cite
|
Sign up to set email alerts
|

Structure of calliterpenone hemihydrate

Abstract: 16a, 17-Dihydroxy-13fl-kauran-3-one,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Ultimately, four structures were obtained from this extract. The crystal structure of calliterpenone ( 1 ) (Figure ) was obtained directly from the microarrayed TEM grid . High-quality microcrystals of calliterpenone monoacetate ( 2 ) were obtained after additional recrystallization, which provided the first crystal structure of this complex diterpene natural product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, four structures were obtained from this extract. The crystal structure of calliterpenone ( 1 ) (Figure ) was obtained directly from the microarrayed TEM grid . High-quality microcrystals of calliterpenone monoacetate ( 2 ) were obtained after additional recrystallization, which provided the first crystal structure of this complex diterpene natural product.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of calliterpenone ( 1 ) ( Figure 3 ) was obtained directly from the microarrayed TEM grid. 36 High-quality microcrystals of calliterpenone monoacetate ( 2 ) were obtained after additional recrystallization, which provided the first crystal structure of this complex diterpene natural product. The structure of a new polymorph of 5-hydroxy-4′,7-dimethoxy-flavone ( 3 ) was also resolved, as well as a polymorph of a presumed plasticizer phthalate 4 .…”
Section: Resultsmentioning
confidence: 99%
“…C.C. Wong introduced inhomogeneities into the textile structure by randomly moving the tow paths and studied influence on the permeability for non-crimp fabric and plain weave models [8]. Long Li showed that the change of the fiber orientation and fiber volume fraction leads to the variety of permeability and, as a consequence, to the resin-rich areas in the composite and mechanical properties decreasing [9].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of calliterpenone (1) (Figure 3) was obtained directly from the microarrayed TEM grid. [25] High quality microcrystals of calliterpenone monoacetate…”
mentioning
confidence: 99%